Klima-Morphologische Arbeiten in Äthiopien im Frühjahr 1953: Beiträge zur Geomorphologie der Klimazonen und Vorzeitklimate X - Büdel, Julius (ERDKUNDE, 1954)
The aim of this paper is to show how the three Ethiopian high plateaux, the Amhara, Kaffa, and Somali highlands, which make up the largest single highland of Africa, can be systematically divided, both horizontally and vertically, into climatically controlled landform zones. In addition to the landforms determined by the present climate, landforms can be distinguished in each of these zones which are due either to a past climate, the climate of a pluvial period, or to human interference with the morphological processes. The lowland which surrounds these highlands is characterized by the contrast between the arid tropical zone, the Danakil Desert, in the north east, and the humid tropical zone of sheet erosion in the west and south. The characteristic features of these two zones do not differ from those of the rest of the Sahara and the Sudan. The humid tropical zone extends up to 2000—2500 m. in altitude and shows characteristic tropical features, such as a predominance of chemical weathering and laterite formation, the presence of inselberge, and the existence of streams whose load contains little coarse material, and which show a tendency towards the formation of steps and cataracts. In this zone no morphologically important traces of a pluvial period are found. Even during the glacial periods the temperature of this warm equatorial zone was lowered only by about 4 ° C and never fell below freezing point; the contemporaneous increase in precipitation, which clearly was not very great in this area, also had little morphological effect. It seems that in this belt the same morphological processes have been active from the pliocene, through the ice age, to the present. Under the influence of human use, however, the laterites of this belt show a tendency towards soil erosion with the formation of gullies and subsequently of bad lands. Above this zone lies the Dega Zone which extends from 2000—2500 m. to the upper limit of forest at 4200 m. As in the first zone the streams contain little coarse material in their load and have little downcutting power, while showing a tendency to form valley steps and cataracts. The laterites are replaced by deep and very fertile black soils with great capacity for absorbing water and a tendency towards solifluxion. In a former, more humid climatic period, probably the last pluvial period, pronounced solifluxion occurred down to an altitude of 2700-2600 m. even on slopes of only 3 ° gradient. Since even during the pluvial period frost was certainly not effective below 3500 m. we have here over a wide area the effects of soil creep of water-saturated soil without the influence of frost action. The resulting set of pluvial landforms, which consist of hills and shallow valleys, is clearly distinct from that of the lower sheet-erosion zone. Where there is a natural mountain forest cover, soil creep is at present limited to slopes of over 30 As a result of agriculture soil creep has, however, been revived in a superficial and less pronounced form on slopes of over 7°. This man-induced soil creep also affects whole slopes; nowhere are there any indications of linear soil erosion and formation of bad lands in the black soil of the Dega Zone. There is a clear association of the Christian- Amharian plough culture with these soils. The highest or rock waste zone in which frost is morphologically effective begins at 4300 m. The snow line, which today would be at about 4800 m. is now at a greater altitude than is reached by the Ethiopian mountains, but the snow line of the glacial period was about 700 m. lower at 4000-4200 m. In the lowland, during the pluvial periods, the zone of humid climate advanced northwards into the desert area; this is shown by a number of fossil gravel sheets of about a thousand sq.km. They date from two pluvial periods and are situated on the western margin of the Danakil Desert towards the Amhara Highland. The eastern part of Danakil on the Red Sea coast, which is today also extremely arid, was probably desert-like even during the pluvial periods. The landforms of volcanic origin which make up the greatest part of the Ethiopian Highland are to be subdivided into five successive age groups on the basis of the degree of preservation of their original features. The last two of these groups come entirely within the pleistocene and holocene periods. These still show the original volcanic features and have not yet become part of any climatically controlled landform zone. Even in case of the third group, which is of late pliocene to early pleistocene age, the original volcanic forms have barely been sufficiently modified to justify their inclusion in such a zone. The still older groups, however, fall clearly into one of these zones, but in comparison with the third group, a period of time ten times longer has been necessary for their modification. All the large lakes of the Ethiopian g r a b e n and the highlands, in particular Lake Tana, owe their existence to the blocking of the drainage by the more recent volcanic eruptions. Since they are situated in the humid tropical lowland zone they show no clear traces of higher levels during pluvial periods. In contrast to these lakes, numerous higher marine terraces due to eustatic changes occur on the west coast of the Red Sea between Suez and Jibuti; but in many cases these are tilted and raised as a result of recent tectonic disturbances. The highest terrace so far recognised, which still preserves its form as a coral ledge, lies at an altitude of 385 m, in the Danakil Desert but it may possibly be earlier, i. e. of pliocene age.